Acute Lymphoblastic Leukemia with t(4;11)(q21;q23)/KMT2A-AFF1 Translocation: The Results of Allogeneic Hematopoietic Stem Cells Transplantation in Children and Adults - TL Gindina; NN Mamaev; OV Paina; AS Borovkova; PV Kozhokar’; OA Slesarchuk; YaV Gudozhnikova; EI Darskaya; AL Alyanskii; SN Bondarenko; LS Zubarovskaya; BV Afanas’ev (Клиническая онкогематология)
Aim. The aim was to evaluate the results of the allogeneic hematopoietic stem cells transplantation (allo-HSCT) in children and adults with the most prognostically unfavorable acute lymphoblastic leukemia (ALL) with t(4;11)(q21;q23)/KMT2A-AFF1 translocation.